Microbial biomass and activity in high elevation (>5100 meters) soils from the Annapurna and Sagarmatha regions of the Nepalese Himalayas - King, Andrew J; Karki, Debendra; Nagy, Laszlo; Racoviteanu, Adina; Schmidt, Steve K (Himalayan Journal of Sciences, 2011)
High elevation subnival-zone soils are increasing in spatial extent in the Himalayas due to glacial retreat and grazing pressures. These seemingly barren soils actually harbor significant microbial diversity but have remained mostly unstudied in all of the major mountain ranges of the Earth. Here we describe a preliminary survey of subnival-zone soils and one vegetated high-elevation soil in the Annapurna and Sagarmatha regions of the Nepalese Himalayas. We examined microbial biomass and activity as well as key microclimatic and edaphic variables that may control microbial activity in these soils. Microbial biomass carbon levels were the lowest ever reported for any soil to date, whereas microbial nitrogen and soil enzyme activities were similar to levels measured in previous studies of subnival-zone soils of Peru and Colorado. Our initial studies also indicate that soil water availability is the primary limiting factor for life in these high-elevation soils. Key words: Microbial; soil; biogeochemistry; subnival; extracellular enzymes; microbial biomass DOI: http://dx.doi.org/10.3126/hjs.v6i8.2303 Himalayan Journal of Sciences Vol.6 Issue 8 2010 pp.11-18